Continuing the conversation among the words: Breyten Breytenbach’s translation strategy in Oorblyfsel/ Voice Over - Kirsten, Elzet (Stellenbosch Papers in Linguistics Plus, 2015)
Breyten Breytenbach’s bilingual collection of poems, Oorblyfsel/ Voice Over (2009), consisting of twelve poems published with the Afrikaans version on the left page and the corresponding English version on the right, shows some notable differences between the two versions of each poem. This article examines the unusual translation strategy of “re-tracing” (Odendaal 2011) that Breytenbach used to produce this collection of poems. Three concepts from literary theory, the ‘contact zone’ (Pratt 1987, 1992), the ‘in-between’ (Bhabha 1993) and the ‘remainder’ (Lecercle 1990), are discussed as tools which can be used to understand this strategy. In light of these three concepts, the two versions of the twelfth poem, simply named 12, are analysed in order to illustrate and understand the effect of Breytenbach’s strategy on the interpretation process that this collection of poems invites the bilingual reader to take part in.